The Financial Risk Reduction Provided by Ghana’s National Health Insurance Scheme - Raju, Dhushyanth; Younger, Stephen D. (World Bank, Washington, DC, 2022)
This paper estimates the monetary value of financial risk reduction associated with membership in Ghana’s National Health Insurance Scheme, based on recent national household survey data. The paper compares the risk premiums for distributions of out-of-pocket healthcare expenditures with and without insurance and find that the difference is small. This does not mean that the National Health Insurance Scheme has no value to members. Indeed, the findings show that the insured pay significantly less for healthcare than the uninsured on average. But that average reduction does not translate into a reduced spread of consumption net of out-of-pocket healthcare expenditures. Thus, the benefit of the National Health Insurance Scheme is entirely a transfer benefit, not a reduction in financial risk.